2012
DOI: 10.1124/dmd.112.049601
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization and Antiviral Effect of Efavirenz Metabolites in Blood Plasma, Seminal Plasma, and Cerebrospinal Fluid

Abstract: Efavirenz (EFV) is one of the most commonly prescribed antiretrovirals for use in the treatment of human immunodeficiency virus (HIV) infection. EFV is extensively metabolized by cytochrome P450 to a number of oxygenated products; however, the pharmacologic activity and distribution of these metabolites in anatomic compartments have yet to be explored. The systemic distribution of EFV oxidative metabolites was examined in blood plasma, seminal plasma, and cerebrospinal fluid from subjects on an EFV-based regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 39 publications
3
45
0
Order By: Relevance
“…Overall, the majority of the studies so far have been restricted to the phase I metabolites (Cho et al, 2011;Avery et al, 2013) even though, as we will show, these metabolites are present in vivo at much lower levels than phase II metabolites.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Overall, the majority of the studies so far have been restricted to the phase I metabolites (Cho et al, 2011;Avery et al, 2013) even though, as we will show, these metabolites are present in vivo at much lower levels than phase II metabolites.…”
Section: Introductionmentioning
confidence: 80%
“…1G). The 8,14-di-OH-EFV has been barely detected in plasma (Avery et al, 2013). Mixed sulfate-glutathione diconjugates of EFV have also been detected in humans (Mutlib et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the scope of the present study was not to elucidate the mechanistic details, it is assumed that either intracellular protein or tissue binding might limit the back transfer of EFV and 8OHEFV from PBMCs to the plasma compartment. EFV is known to be highly bound to plasma proteins (Ͼ99%) and tissue structures (28,29) and 8OHEFV has been reported to have protein binding similar to that of EFV (30). However, further in vitro-supported studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not a common practice to collect semen in human ADME studies, detection of drugs and their metabolites in semen has been reported previously, particularly in patients with HIV (Ette et al, 1988; Taylor and Pereira, 2001;Avery et al, 2013). Semen was evaluated since subjects in prior studies had reported semen discoloration after taking KAE609 at higher doses.…”
Section: Discussionmentioning
confidence: 99%